Dampak Perubahan Anggaran, Fiscal Stress, dan SiLPA terhadap Penyerapan Anggaran Pemerintah Daerah: Studi pada Kabupaten/Kota di Sumatera Selatan - Marselita Jayenchi; Maria Maria; Indra Satriawan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of Budget Changes, Fiscal Stress, and SiLPA on Budget Absorption in Regency/City Governments in South Sumatra Province in 2019-2023. The population in this study is all Regional Governments consisting of 13 Regencies and 4 Cities in South Sumatra Province using the saturated sampling technique method. The data used in this study is secondary data in a time series format sourced from the official website of the Audit Board of the Republic of Indonesia with an observation year of 5 years. The data analysis methods used in this study are descriptive statistics and multiple linear regression. Based on the results of data processing through the EViews 12 for Windows software that has been analyzed, it is concluded that the variables of Budget Change, Fiscal Stress, and SiLPA have a positive and significant effect on Budget Absorption in Regency/City Governments in South Sumatra Province.